A high-gain microstrip grid array antenna on low temperature co-fired ceramic for 60-GHz applications - Zirath, Herbert (2013)
This paper presents a high-gain microstrip (MS) grid array antenna (GAA) on low temperature co-fired ceramic (LTCC). The high-gain MS GAA includes four sub-antennas. Dimensions of the sub-antenna are 15 × 15 × 0.5 mm3, which is composed of four sub-arrays. Preliminarily tested results show that the sub-antenna features fractional impedance bandwidth (BW) 58 - 60 GHz and 62 - 63.5 GHz, 3-dB gain BW 59.8 - 65 GHz with the maximum gain 17.3 at 64.3 GHz, and vertical beams in the broadside direction from 57 - 64 GHz. The highgain MS GAA has dimensions of 30 × 30 × 0.5 mm3. Simulated results show that it has impedance BW 55 - 64.6 GHz, 3-dB gain BW 57.5 - 64.8 GHz with the maximum gain of 22.8 dBi at 60.8 GHz, and vertical beams in the broadside direction from 57 - 64 GHz. It is a capable candidate for 60-GHz applications, and even higher frequency band like the 140 and 220 GHz.